Herbicide accumulation and evolution in reservoir sediments - Devault, Damien A.; Gérino, Magali; Laplanche, Christophe; Julien, Frédéric; Winterton, Peter; Merlina, Georges; Delmas, François; Lim, Puy; Miguel Sánchez-Pérez, José; Pinelli, Eric (The Science of the total environment, 2009)
The aim of the present study was to understand the effect of reservoir configurations on sediment pesticide fate. Two dams were selected on the River Garonne, in southwest France: Carbonne and Golfech, both with reservoirs subject to accumulation of herbicide-contaminated sediment. They are situated upstream and downstream respectively of an agricultural and urban area: the Mid-Garonne. The results presented include pesticide concentrations and C/N ratios in the smaller sediment particles (< 2 mm) and values of oxygenation and herbicide concentrations in the water. The dynamic behaviour of sediment in the reservoirs is discussed. The present study shows that the theoretical lifespan (weak remanence in vitro) and the results actually observed in the sediment are conflicting. Pesticide contamination in Carbonne indicates conservation, even accumulation, of herbicide molecules while in Golfech transformation processes clearly dominate. The hydromorphological position of Golfech reservoir, i.e. located at the junction of two rivers with contrasting hydrological regimes and very different oxygenation conditions, leads to accelerated pesticide desorption or degradation. Unfortunately, this configuration is rare.